Influence of macroeconomics factors and legal stability to the insurance growth in the ASEAN-5 countries - Hui, Shan Lee; Fan, Fah Cheng; Shyue, Chuan Chong; Bik, Kai Sia (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper examines the influence of legal stability and macroeconomics factor to the non-life insurance development. In light of the growing significance of foreign direct investment (FDI) and trade that stimulate insurance sector, and the stress placed on legal stability of the countries, investigating the role of legal stability is crucial to sustain a country’s financial development. This study employs a panel data analysis spanning 20 years in the selected developing countries. The findings suggest that higher trade, higher income, higher stock market trading activities and higher availability of finance credit will enhance the non-life insurance development. Legal stability such as enhancement on the property right and government integrity will improve the non-life insurance development. When the legal environments in emerging countries are more stable, the FDI and stocks market will become more encouraging and stimulate non-life insurance development. The policy makers should improve the legal stability in emerging countries to improve the financial development for minimizing the gap with developed countries. This study includes the institutional factors components in addition to the macroeconomics factors could provide a complete picture towards the improvement of non-life insurance development in emerging and transition countries.